B cell and antibody responses in bovine tuberculosis - Klepp, Laura Ines; Blanco, Federico Carlos; Bigi, María Mercedes; Vazquez, Cristina Lourdes; Garcia, Elizabeth Andrea; Sabio Y Garcia, Julia Veronica; Bigi, Fabiana (MDPI, 2025)
The development of vaccines and effective diagnostic methods for bovine tuberculosis requires an understanding of the immune response against its causative agent, Mycobacterium bovis. Although this disease is primarily investigated and diagnosed through the assessment of cell-mediated immunity, the role of B cells and antibodies in bovine tuberculosis has been relatively undervalued and understudied. Current evidence indicates that circulating M. bovis-specific antibodies are not effective in controlling the disease. However, local humoral immune responses may contribute to either defence or pathology. Recent studies in animal models and cattle vaccine trials suggest a potential beneficial role of B cells in tuberculosis control. This review discusses the role of B cells and antibodies in bovine tuberculosis and explores antibody-based diagnostics for the disease, including traditional techniques, such as different ELISA, new platforms based on multiple antigens and point-of-care technologies. The high specificity and sensitivity values achieved by numerous antibody-based tests support their use as complementary tests for the diagnosis of bovine tuberculosis, especially for identifying infected animals that may be missed by the official tests.